Students bridging the diversity gap in dermatology-A mixed methods study of medical education - Shihan Salihu; Harmony Hart; Christopher Wort; Musarrat M. Reza (Wiley, 2024)
Abstract Background After noticing a lack of diversity in pictures for skin conditions and dermatology teaching, seven medical students applied for funding from the University of Exeter to design a project with the aim of expanding their dermatology knowledge through developing diverse teaching resources and assessing knowledge using innovative evaluation methods. Students then tested their project by raising awareness about common skin conditions and their presentation on different skin colours to the public in Exeter. Objectives This paper aims to reflect on and evaluate the experience of medical students in developing and implementing this project, with a focus on the significant positive impact it had on their dermatological knowledge and practical ability to assess skin conditions on diverse skin tones. Methods Each team member was asked to complete a survey to self‐assess critical skills before and after participating in the project and write a post‐event reflective piece. The responses to the survey and reflective pieces were further analysed for specific themes. Results All members perceived a significant improvement in three common themes: (i) bridging the knowledge gap, (ii) gaining confidence in designing innovative resources and (iii) enhancing communication skills. The survey and reflective pieces also identified areas of improvement in the project. Conclusions Beyond expanding the dermatology knowledge of medical students, the project encouraged critical thinking and proactiveness as future clinicians. Medical students perceived improvements in key skills such as effective communication, public speaking and developing innovative teaching resources. Medical schools must create opportunities to enable such student‐led projects and embed inclusion and diversity in the medical curriculum so that future clinicians are well‐equipped to serve a rapidly diversifying population. This project has now received further funding and is being expanded to create a digital resource pack for all medical school educators and students.